Clinical and Biologic Characteristics and Outcomes in Young and Middle‐Aged Patients With Laryngeal Cancer: A Retrospective Cohort Analysis. (25th January 2022) - Geng, Calvin X.; Tanamal, Priscilla; Arvisais‐Anhalt, Simone; Tomasino, Massimo; Gheit, Tarik; Bishop, Justin A.; Palsgrove, Doreen N.; Wang, Ellen; Salley, Jordan R.; Tibbetts, Kathleen M.; Sumer, Baran D.; Tillman, Brittny N.; et al.
Abstract : Objective: To describe the clinical and biologic characteristics and outcomes of young and middle‐aged (YMA; <65 years) patients according to the presence or absence of traditional risk factors for laryngeal cancer. Study Design: Retrospective cohort analysis. Setting: Single‐institution academic medical center. Methods: Patients without a history of clinically significant tobacco use or heavy alcohol use were defined as "nontraditional": ≤5 pack‐years, ≤5 years smoked, ≤14 alcoholic drinks per week, and ≥15‐year interval from last tobacco abuse use to diagnosis. Remaining patients were categorized as "traditional." Select tumor samples were evaluated for bacterial and viral DNA by multiplex polymerase chain reaction. Results: Seventy‐eight YMA patients with primary laryngeal squamous cell carcinoma were identified, 23% (n = 18) of whom were nontraditional. Nontraditional patients were younger than traditional patients (median age, 51 vs 59 years; P <. 001). Twenty‐eight tumors were prospectively tested for human papillomavirus (HPV), and nontraditional patients were more likely to exhibit high‐risk HPV (57% vs 5%, P <. 01). Among 17 select tumors (nontraditional, n = 8; traditional, n = 9), 35% exhibited HPV16 (nontraditional, 63%; traditional, 11%; P =. 05). Other viruses were identified but did not differ according to risk status: herpesviruses (40%) and Merkel cell polyomavirus (7%). Chlamydia, β‐HPV, and γ‐HPV DNA was not detected in any samples. Median length of follow‐up was 42 months. On adjusted analyses, nontraditional patients exhibited nonsignificantly improved overall survival (hazard ratio, 0.24 [95% CI, 0.03‐1.82]; P =. 17) and disease‐free survival (hazard ratio, 0.34 [95% CI, 0.10‐1.23]; P =. 08) as compared with traditional patients. Conclusion: Almost one‐quarter of YMA patients lacked characteristic risk factors for laryngeal squamous cell carcinoma, and their tumors exhibited a higher prevalence of high‐risk HPV. The significance of HPV16 and other tumor viruses with outcomes in nontraditional patients should be evaluated further.